EVALUASI TATA KELOLA DAN AUDIT SISTEM INFORMASI RUMAH SAKIT GANESHA DENGAN MENGGUNAKAN KERANGKA KERJA COBIT 5 - Dewa Gede Eka Krisna Prandana; A.A. Istri Ita Paramitha; I Gede Juliana Eka Putra (Journal of Applied Management and Accounting Science, 2019)
Ganesha Hospital has implemented IT using SIMRS Ganesha in collaboration with Vendor CV Nayaka to create the system. But there are still problems in the application of the Ganesha SIMRS. In its application there are still errors in recording the patient's medical records that have an impact on the determination of patient medication as well as inputting patient administration payment data, this problem is included in the EDM4 domain (ensuring resource optimization) and APO7 (managing human resources), BPJS verification issues, namely for BPJS verification. health cost control and the absence of BPJS system integration, this problem is included in the DSS6 domain (managing and controlling business processes) and patient database maintenance has not been done, and if maintenance is not done, then the data in Ganesha Hospital is invalid this problem is included in the domain MEA3 (monitor, evaluate and evaluate conformity with external needs). Because there are still obstacles in the information technology governance system at Ganesha Hospital it is deemed necessary to be studied more deeply by evaluating governance. The method of research carried out based on the COBIT 5 framework uses the EDM4, APO7, DSS6, and MEA3 domains. Furthermore, calculations are performed with the ISO / IEC 15504 capability model. The results of the maturity of IT governance at SIMRS Ganesha are obtained with an average of 2.77 and are at level 3 (Established) with an average gap value of 2.23. To improve IT governance at Ganesh Hospital, it must improve governance in the EDM4, APO7, DSS6, and MEA3 domains according to recommendations.